Tindak Pidana Pemerkosaan Dengan Kekerasan Yang Dilakukan Secara Bersama-Sama Ditinjau Dari Perspektif Psikologi Kriminal (Studi Putusan Nomor Xx/Pid.B/2022/Pn.Tlk) - Shilvirichiyanti (Faculty of Law Universitas Lancang Kuning, 2023)
Factors causing the crime of rape with violence committed jointly (study decision Number XX/Pid.B/2022/PN.Tlk? What is the perspective of Criminal Psychology towards the crime of rape with violence committed jointly (study decision Number xx/Pid.B/2022/PN.Tlk)? This research uses library research, namely a type of documentation research to obtain data by tracing and studying the decision files of the Telukkuantan District Court. The nature of this research is analytical descriptive The data obtained will be arranged descriptively, then the researcher will analyze it qualitatively, namely the procedure for solving the problem studied by presenting the data obtained from the field, both primary data and secondary data, in the form of sentences, not in the form of arranged numbers. logically and systematically without using statistical formulas. The factors that cause the crime of rape with violence to occur together (study Decision Number XX/Pid.B/2022/PN.Tlk) are environmental factors, promiscuity, sexuality. , the influence of technology and alcoholic beverages. Criminal Psychology plays an important role in the Crime of Rape with violence, that there are psychological factors that influence humans in acting both social and asocial, or in other words that crime or in this case the Crime of Rape is an act that is against the law. determined by the institutions found in humans themselves.